Relaxation effects on thermoelastic interactions in a transversely isotropic unbounded body with a spherical cavity subjected to periodic loading - Mukhopadhyay S. (My University, 2025)
The present work is attempted to understand the effects of thermal relaxation parameters on thermoelastic interactions in an unbounded body with a spherical cavity which is acted upon by a cyclically varying stress. The distributions of displacement, temperature and stress fields are firstly found out analytically for both the cases of conventional and generalized theories of thermoelasticity and then the numerical values of the field variables for a particular material are computed. The effects of thermal relaxation parameters involved in the generalized theories of thermoelasticity are studied with the help of graphical presentation.